Phosphate-Starvation-Inducible S-Like RNase Genes in Rice Are Involved in Phosphate Source Recycling by RNA Decay - Gho, Yun-Shil; Choi, Heebak; Moon, Sunok; Song, Min Yeong; Park, Ha Eun; Kim, Doh-Hoon; Ha, Sun-Hwa; Jung, Ki-Hong (Frontiers in Plant Science, 2020)
The fine tuning of the phosphate (Pi) for the enhanced use efficiency, has been a challenging subject for long agricultural history in rice as a major crop plant. Among ribonucleases (RNases), RNase T2 family is broadly distributed across kingdoms but it has been known little on the substrate specificity compared to RNase A and RNase T1 families. Class I and class II of RNase T2 family are defined as the S-like RNase (RNS) family and have showed the connection to Pi recycling in Arabidopsis while the class III has been involved in self-incompatibility. In this study, we first carried out the phylogenetic analysis of eight rice and five Arabidopsis RNS genes, and identified mono-specific class I and dicot-specific class I RNS genes, suggesting the possibility of functional diversity between class I RNS family members in monocot and dicot species through evolution. We then compared the in silico expression patterns of all RNS genes in rice and Arabidopsis under normal and Pi deficiency conditions, and further confirmed the expression patterns of rice RNS genes via qRT-PCR analysis. Subsequently, we found that most of OsRNS genes were differentially regulated under Pi deficiency treatment. Association of Pi recycling by RNase activity in rice was confirmed by measuring total RNA concentration and ribonuclease activity of shoot and root samples under Pi-sufficient or Pi-deficient treatment during 21 days. The total RNA concentrations were decreased by <60% in shoots and <80% in roots under Pi starvation, respectively, while ribonuclease activity increased correspondingly. We further elucidate the signaling pathway of Pi starvation through upregulation of the OsRNS genes. The 2kb promoter region of all OsRNS genes with inducible expression patterns under Pi deficiency contains a high frequency of P1BS cis-acting regulatory element known as the OsPHR2 binding site, suggesting that OsRNS family is likely to be controlled by OsPHR2. Finally, the dynamic transcriptional regulation of OsRNS genes by overexpression of OsPHR2, ospho2 mutant and overexpression of OsPT1 lines involved in Pi signaling pathway suggests the molecular basis of OsRNS family in Pi recycling via RNA decay under Pi starvation.